Assessment of Thyroid Function in Early Pregnancy - Rahman, Mohammad Saifur; Sultana, Sadia; Nazneen, Ayesha (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: Thyroid disorders are commonly observed in pregnancy. Thyroid hormones play an important role in embryogenesis and fetal development. The fetus is completely dependent on the mother for thyroid hormone in first trimester. About 10% of all pregnant women can be affected by thyroid disorders during pregnancy. Thyroid function abnormalities in pregnancy are a challenge for the concerned physicians. The objective of this study was to assess the maternal thyroid function in first trimester of pregnancy. Patients and Methods: A descriptive cross sectional study was carried out at the Combined Military Hospital (CMH), Dhaka over a period of one year from January 2013 to December 2013 to see the serum FT3, FT4, TSH, thyroid antibodies level and common thyroid disorders in pregnancy. A total of 138 pregnant women in their first trimester (up to 12 weeks) of pregnancy with an age range of 18-35 years were enrolled in this study. Pregnant women with known thyroid disorder and on treatment and pregnancy more than three months were excluded. Measurement of serum FT3, FT4, TSH, Anti TPO-Ab and Anti TG-Ab were done in each patient at the time of enrolment. Ultrasonography of each patient was done for confirmation of pregnancy and correlation of gestational age. Results: Among 138 pregnant women, subclinical hypothyroidism was detected in 10 (7.2%) patients and subclinical hyperthyroidism was detected in 3 (2.2%) patients. Mean difference of the investigation findings were not statistically significant among primi and multi gravida. TPO-Ab and TG-Ab difference were statistically significant between two age groups. Conclusion: Subclinical thyroid disorders are fairly high among pregnant women. Correct diagnosis in early pregnancy and prompt treatment will bring an excellent prognosis for both mother and offspring. Bangladesh J. Nuclear Med. 19(2): 98-102, July 2016